Abrasion Behaviour of Different Charcoal Toothpastes When Using Electric Toothbrushes - Andreas Greuling; Johanna Maria Emke; Michael Eisenburger (MDPI AG, 2021)
Objectives: The purpose of this in vitro study was to compare the abrasion behaviour of different charcoal toothpastes when brushing with electric toothbrushes on human enamel. Materials and Methods: A self-designed brushing machine was built using six commercially available electric toothbrushes in abrasion chambers. Each chamber was constantly supplied with a toothpaste-water mix. Pieces of human enamel, which were embedded in PMMA, were brushed for 4 h. Before and after brushing, profilometer measurements were performed in order to determine the substance loss due to brushing. Results: The following calculated mean removal values (mean ± SD) were found: (4.6 ± 0.6) µm (Group C: Splat Blackwood), (3.2 ± 0.9) µm (Group D: Curaprox Black is White), (2.3 ± 0.7) µm (Group B: Sensodyne Pro Schmelz), (1.7 ± 0.6) µm (Group A: Water), (1.4 ± 0.6) µm (Group E: Prokudent Black Brilliant). A post hoc Tukey HSD test (p = 0.05) showed that the results for Group A/B/E, Group B/D and Group C each lie within subsets that differ statistically significantly from the other subsets. Conclusions: Within the limitations of this in vitro study, it can be stated that some charcoal toothpastes lead to significantly higher abrasion on human enamel, when brushing with electric brushes. Clinical Relevance: As low-abrasion toothpaste is generally advisable, and some charcoal toothpastes should be viewed critically with regard to their abrasive properties.